FACTOR-FACTOR PENYEBAB ANAK PUTUS SEKOLAH DI DESA BENTIANG MADOMONG KECAMATAN AIR BESAR KABUPATEN LANDAK - Lestari, Yessi; Matsum, Junaidi H; Aminuyati, Aminuyati (Universitas Tanjungpura, 2023)
The function of here study is to analyze (1) element of his toexplanation child to close up our study in Bentian Madmon ordinarysenttlement, Airbesar District, Randall Regency, and (2) the centralelement of children our reason children to drop out of school. Thisresearch was conducted in Bentian Village, Eybesar District, LandacDistrict. The method used in this study is Definition of conditional independent inquiry. The review was assisted with a absolute of 10prisoner in Bentian Madmon Village, Air Besar District, RandakRegency. The dossier assemblage arrangement worn in this study isinformation and documentation using data collection device.to watching pattern and authentication device. Based on goodsscrutiny consequences assisted by the institute, the criterion whychildren in Bentian Madmon Village, Regency Hedgehog, Air BesarDistrict drop out of school, namely (1) are domestic factors, namelychildren's academic ability. already stated sense, sie was cold-bloodedthat effective act scant enthusiasm contemporary in going to school,(2) family economic factors, (3) external factors are environmentalfactors, (4) social aspect, along with (5) health aspect. The largestreasoning why children in Bentian Madmong pace drop out of schoolis its lack of interest in going in school and enviroment or our people.